Characterisation and antimicrobial activity of active polypropylene films containing oregano essential oil and Allium extract to be used in packaging for meat products. Issue 4 (3rd April 2018) - Llana-Ruiz-Cabello, María; Pichardo, Silvia; Bermudez, José María; Baños, Alberto; Ariza, Juan José; Guillamón, Enrique; Aucejo, Susana; Cameán, Ana M.
ABSTRACT: Cooked ham is more prone to spoilage than other meat products, making preservation a key step in its commercialisation. One of the most promising preservation strategies is the use of active packaging. Oregano essential oil (OEO) and Proallium® (an Allium extract) have previously been shown to be useful in polylactic acid (PLA)-active films for ready-to-eat salads. The present work aims to study the suitability of polypropylene (PP) films containing OEO and Proallium® in the preservation of cooked ham. Concerning the technological features of the studied material, no significant changes in the mechanical or optical properties of PP films containing the active substances were recorded in comparison to the PP film without extracts. However, films containing both active substances were more flexible than the control film and less strong, highlighting the plasticisation effect of the natural extracts. Moreover, physical properties changed when active substances were added to the film. Incorporation of 4% Proallium® affected the transparency of the film to a higher extent compared to 8% OEO, undergoing decreases in transparency of 40% and 45%, respectively. Moreover, only the film containing the highest amount of OEO (8%) significantly decreased the thickness. Both active substances showed antibacterial properties; however, Proallium®-active films seemed to be more effective against Brochothrix thermosphacta than PP films containing OEO, with all percentages of Proallium® killing the bacterial population present in the ham after 60 days. In addition, materials containing the lowest Proallium® content exhibited higher acceptability by consumers in the sensory analyses with 63–100% willing to purchase, better even than the control package (56–89%). In fact, 2% of Proallium® obtained the best results in the odour study performed by the panellists.